Tony Award Season 2018 [compact disc]. - Sutton, Adrian, 1967-; Flaherty, Stephen; Urie, Brendon; Loewe, Frederick, 1901-1988; Buffett, Jimmy; Yazbek, David, 1960-; Richmond, Jeff; Anderson-Lopez, Kristen; Summer, Donna; Brown, Jason Robert; Marsalis, Branford; Lloyd Webber, Andrew, 1948-; et al. (Broadway Records, 2018)
The 2017-2018 Broadway season is celebrated with a compilation that includes tracks from this year's Tony-nominated musicals as well other hits, including Escape to Margaritaville and Prince of Broadway.